Phase‐rectified signal averaging for intrapartum electronic fetal heart rate monitoring is related to acidaemia at birth. (7th February 2014) - Georgieva, A; Papageorghiou, AT; Payne, SJ; Moulden, M; Redman, CWG
<x xml:space="preserve">Abstract</x> Objective Recent studies suggest that phase‐rectified signal averaging (PRSA), measured in antepartum fetal heart rate (FHR) traces, may sensitively indicate fetal status; however, its value has not been assessed during labour. We determined whether PRSA relates to acidaemia in labour, and compare its performance to short‐term variation (STV), a related computerised FHR feature. Design Historical cohort. Setting Large UK teaching hospital. Population All 7568 Oxford deliveries that met the study criteria from April 1993 to February 2008. Methods We analysed the last 30 minutes of the FHR and associated outcomes of infants. We used computerised analysis to calculate PRSA decelerative capacity (DCPRSA), and its ability to predict umbilical arterial blood pH ≤ 7.05 using receiver operator characteristic (ROC) curves and event rate estimates (EveREst). We compared DCPRSA with STV calculated on the same traces. Main outcome measure Umbilical arterial blood pH ≤ 7.05. Results We found that PRSA could be measured in all cases. DCPRSA predicted acidaemia significantly better than STV: the area under the ROC curve was 0.665 (95% CI 0.632–0.699) for DCPRSA, and 0.606 (0.573–0.639) for STV (P = 0.007). EveREst plots showed that in the worst fifth centile of cases, the incidence of low pH was 17.75% for DCPRSA but 11.00% for STV (P < 0.001). DCPRSA was not highly correlated with STV. Conclusions DCPRSA of the FHR can be measured in labour, and appears to predict acidaemia more accurately than STV. Further prospective evaluation is warranted to assess whether this could be clinically useful. The weak correlation between DCPRSA and STV suggests that they could be combined in multivariate FHR analyses.